Design Technique on Speed Control Combined with an Inertial Element for Vibration Suppression - Guoguang Zhang; Shuntai Xie; Peng Hou; Xiaoguang Wang (Machines, 2025)
The suppression of mechanical resonance stands as the most crucial issue in enhancing system performance. In this study, based on a speed control system, the mechanisms of vibration suppression both with and without a first-order inertial element are analyzed and compared, and a pole assignment method featuring an identical radius is put forward. Through an optimized design of pole assignment, the constraint conditions, control parameters, and applicable boundary of the first-order inertial element are explicitly derived in an analytical form. These derived results possess clear design significance and are very convenient for practical use. It is demonstrated that speed control with the first-order inertial element can effectively improve the underdamping performance. The proposed control method and the constrained optimization design of pole assignment are validated through experiments.